PURPLE CABBAGE EXTRACTS (Brasicca oleracea L) AS TOFU’S FORMALIN INDICATORS - Sumiati Sumiati (Integrated Lab Journal, 2019)
Tofu is a food that is in great demand by people in Indonesia. In processing tofu, producers usually use formalin as a preservative to maintain storage time. The use of formalin in food can cause poisoning. This study aims to determine the method that can be used to unlock the potential of purple cabbage plants (Brasicca oleracea L) as an alternative natural indicator in the qualitative examination of formalin and to obtain experimental results using purple cabbage extract (Brasicca oleracea L) as an alternative natural indicator of deep formalin examination know. Purple cabbage (Brassica oleracea L) is a kind of typical vegetable plant. The typical color is caused by the presence of anthocyanin. This anthocyanin can be used as an alternative natural indicator. Qualitative formalin examination using purple cabbage extract and formalin test kit. The tofu samples used were tofu samples containing 0%, 1%, 0.5%, 0.25%, 0.12%, 0.06% and 0.03% formalin. The solvent used for purple cabbage extract is distilled water. The parameters observed were color changes. The results showed that purple cabbage extract can be used as an alternative natural indicator on formalin examination in tofu. Tofu that does not contain formaldehyde undergoes a change in color from purple to pink after dropping purple cabbage extract, while tofu containing formalin does not change color after dropping purple cabbage extract.